Retention and clearance of inhaled ceramic fibres in rat lungs and development of a dissolution model. Issue 4 (April 1994) - Yamato, H; Hori, H; Tanaka, I; Higashi, T; Morimoto, Y; Kido, M
Abstract : Male Wistar rats were exposed to aluminium silicate ceramic fibres by inhalation to study pulmonary deposition, clearance, and dissolution of the fibres. Rats were killed at one day, one month, three months, and six months after the termination of exposure. After exposure, fibres greater than 50 microns in length were seen with a scanning electron microscope in the alveolar region of the lung. Fibres were recovered from the lungs with a low temperature ashing technique and their number, diameter, and length were measured by scanning electron microscopy. The number of fibres remaining in the lungs declined exponentially with time after exposure and their silicon content also fell. The geometric median diameter of fibres decreased linearly with time. By six months after exposure, the surface of fibres recovered from the lungs had an eroded appearance. The results suggest that ceramic fibres are physically cleared from the lung and that they show signs of dissolution. Finally, the results were used to develop a theoretical model of fibre dissolution that gives a satisfactory fit to the experimental data.